Aplicación de técnicas para el logro de hábitos de lectura, en el bloque 6 rimas y cuentos, en el área de lengua y literatura, en los niños y niñas de quinto grado de educación general básica de la escuela Pompilio Reinoso Jaramillo del barrio Sauces Norte de la ciudad de Loja, período académico 2013-2014 - Rojas Cruz, Zuleyma Johanna (2015)
The present thesis: application of techniques for the achievement of habits of reading, in the block 6 rhymes and tales, in the area of language and literature, in the children and girls from fifth grade of education general basic school "Pompilio Reinoso Jaramillo" of the neighborhood willows North of the city of Loja, 2013-2014 academic period, general objective is to contribute to the implementation of techniques for the achievement of reading habits in the block 6 rhymes and stories in the area of language and literature in fifth-graders Pompilio Reinoso Jaramillo school basic General education. The methods used to carry out this investigation were: Cross, quasi-experimental design, comprehensive, analytical, synthetic method, participatory, models or proactive, workshop and the method of comprehensive evaluation, and as techniques used: surveys applied to 24 students and a teacher, with the results of the research that the majority of students; Sometimes they practice rapid reading since they do not have reading habits; they prefer easy readings as the tales; If they apply reading skills not used properly with the application of techniques of reading and model strategies to achieve the habit of reading through the workshop method, it profited directly to students and teachers, helping to reduce the difficulties that students present in the application of reading skills, proven by Pearson's r.